2022
DOI: 10.1002/csr.2319
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a firm's corporate social responsibility on firm–supplier relationships: The effect of secondary stakeholder CSR on inventory days

Abstract: Well-known benefits of corporate social responsibility (CSR) are goodwill and trust.Typically, research states that if a firm engages in CSR activities that benefit stakeholder X, then stakeholder X will reciprocate with higher levels of trust. We advance this line of research by examining whether CSR activities directed to stakeholder X increase the levels of trust between the firm and a different stakeholder, Y. Specifically, we examine the consequences of CSR actions that a firm directs toward non-supplier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 144 publications
0
9
0
Order By: Relevance
“…Likewise, assessing stakeholder needs can significantly impact companies' performance and reputation (Solana‐Ibáñez & Caravaca‐Garratón, 2021). It will also affect the level of trust between the various stakeholders and the company (Groening et al, 2022). As a result, this trade‐off may be difficult for companies, as company behavior during terrorist crises will play a decisive role in stakeholders' approval or dissatisfaction with company behavior.…”
Section: Theoretical Perspectives Literature Review and Hypotheses De...mentioning
confidence: 99%
“…Likewise, assessing stakeholder needs can significantly impact companies' performance and reputation (Solana‐Ibáñez & Caravaca‐Garratón, 2021). It will also affect the level of trust between the various stakeholders and the company (Groening et al, 2022). As a result, this trade‐off may be difficult for companies, as company behavior during terrorist crises will play a decisive role in stakeholders' approval or dissatisfaction with company behavior.…”
Section: Theoretical Perspectives Literature Review and Hypotheses De...mentioning
confidence: 99%
“…The experts reported that work on CSR is increasing which helps the firm to create awareness and to assure the benefits of being socially responsible (Dobele et al, 2014; Groening et al, 2022; Xun, 2013). In the domain of consumers, the CSR impact was mainly not discussed in the literature especially considering them as the important stakeholder of the firms.…”
Section: Review Of Literaturementioning
confidence: 99%
“…When it comes to external factors that impact corporate green governance, external stakeholders like suppliers, the public, and investors push businesses to uphold environmental governance standards [ 7 ] and take on social responsibility in order to reduce wage inequality [ 8 ]. Given the growing interest of green investors and other stakeholders in a company's social and environmental responsibility, the “GCG” can potentially convey signals of environmental protection and draw in green investors[ 9 ].…”
Section: Introductionmentioning
confidence: 99%